First Biosourced Monolithic Macroporous SiC/C Composite Foams (Bio‐SiC/C(HIPE)) Bearing Unprecedented Heat Transport Properties1. Issue 10 (23rd July 2013) - Ungureanu, Simona; Sigaud, Gilles; Vignoles, Gérard L.; Lorrette, Christophe; Birot, Marc; Deleuze, Hervé; Backov, Rénal
<x xml:space="preserve">Abstract</x> For the first time SiC/C composite foams were prepared from concentrated emulsions by carbothermal reduction of biosourced precursors combining sodium silicate by lignin at 1400 °C. The composition of the materials was determined by XRD, FTIR and Raman analyses. Their porous structure was characterized by SEM, mercury intrusion porosimetry, and nitrogen sorption, while their thermal properties were measured by TGA and dynamic DSC. Concerning their heat transport properties, we found out that when the starting lignin content was increased, the final C/Si ratio, the specific surface area and the heat diffusivity increased as well. Its unprecedented high values were attributed to a cooperative effect between radiative heat transfer and the presence of partially graphitized carbon.